A Study on the Mechanical Behavior of a Wind Turbine Foundation with a Constrained Structural Shear Connector - Jingjing Qi; Yining Ye; Lizhong Jiang; Weirong Lü; Beirong Lu; Jidong Wu (Buildings, 2024)
Aiming to solve the problems that a wind turbine foundation with a foundation pipe may suffer from grouting, where the concrete around the interface collapses and the interface disintegrates under a long-term wind load, a kind of wind turbine foundation with a constrained structural shear connector is proposed. In this article, the scaling model tests and a finite element simulation of a traditional stud foundation pipe, perforated steel shear connector foundation pipe, and three groups of constrained structural shear connector foundation pipes with different anchored depths are presented. The force transmission mechanism and damage mechanism of constrained structural shear connector wind turbine foundations are revealed, and the shear resistance of a constrained structural shear connector is analyzed. The influences of buried depth and other parameters on the mechanical properties of the shear connector are also investigated. The results show that the constrained structural shear connector has the advantages of stronger interfacial stiffness and significant force transfer and diffusion, and can more effectively connect the foundation pipe and concrete foundation to work together. It can give full play to the material advantages of concrete and reinforcements, and effectively improve the embedded stiffness and durability of concrete foundations. It can solve the problem of cracks in concrete caused by local pressure. At the same time, it is suggested that the diameter of the surrounding concrete should be in the range of 3 to 4 D, and the embedment depth of the stud should not be less than 0.4 D to give full play to the performance of the constrained structural shear connector.